(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The increasing interest of behavior analysts for the history of this discipline and, consequently, for historical research. Thus, this work is aimed at discussing some considerations about history and historiography of science, with the intent of bringing contributions from these disciplines to the historical research in beharior analysis. For this, some key issues and the production on the history of science and historiography of science will be presented, such as, the complaint on internalism X externalism, the use of whiggist formulations which appeal to the current knowledge of a scientific discipline on a biased approach, and to the definition of historical sources. At the same time, examples of historical research in behavior analysis and behaviorism will be raised to argue on some critical aspects that involve this type of inquiry.